FINANCIAL TECHNOLOGY: PROFIT MAXIMIZATION IN UMKM ACTORS IN THE CITY OF MAKASSAR (STUDIES AT OVO MERCHANTS IN THE CITY OF MAKASSAR) - faradillah, Fifi; Ali, Muhammad; Nohong, Mursalim (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
This study expects to figure out the reaction of UMKM entertainers to the development of monetary innovation or called Monetary Innovation (OVO). What's more, this examination likewise means to figure out how the requirement for the utilization of Monetary Innovation (OVO) in expanding benefits for UMKM entertainers in Makassar City. This exploration is a subjective examination with a phenomenological approach. The information assortment strategy was completed by field studies and documentation. Strategies for information investigation utilizing information decrease procedures, information show and reaching determinations. Test the legitimacy of exploration information utilizing triangulation of information sources. The aftereffects of the review show that the perspective on business directors in regards to fintech is that this is the sort of thing that is vital in business improvement, where the utilization of fintech can work on the installment framework and buyers get added esteem with the presence of different cost limits introduced by the fintech stage. Shoppers never again need to convey cash, essentially use fintech (OVO) to make installments and this is exceptionally gainful for organizations and buyers. Also, the utilization of fintech for UMKM entertainers in the city of Makassar has given an expansion in benefits of around 10-20%. Expanding benefits is surely an extremely persuasive thing in business improvement. This increment can happen because of the utilization of fintech, buyers are progressively urged to make buys because of simple access, extra limits and exchanges that can occur quicker, more secure, more helpful and simplier. This increment can happen because of the utilization of fintech, shoppers are progressively urged to make buys because of simple access, extra limits and exchanges that can occur quicker, more secure, more helpful and more straightforward.